Lipopolysaccharide-induced toll-like receptor 4 signaling in esophageal squamous cell carcinoma promotes tumor proliferation and regulates inflammatory cytokines expression. Issue 2 (20th December 2016) - Zu, Yukun; Ping, Wei; Deng, Taoran; Zhang, Ni; Fu, Xiangning; Sun, Wei
SUMMARY: Emerging evidence suggests toll-like receptor 4 (TLR4) signaling contributes to cancer development and progression. However, the consequences of signaling via the TLR4 pathway in esophageal squamous cell carcinoma (ESCC) are still unclear. Here, we investigated the impact of Lipopolysaccharide (LPS)-induced TLR4 signaling on ESCC cell proliferation, inflammatory cytokines expression, and downstream molecular mechanisms. Seventy-eight ESCC and 26 normal esophageal specimens were analyzed by immunohistochemistry, and two cell lines (Eca-109 and TE-1) were used for in vitro studies. LPS, a natural agonist of TLR4, was used to activate TLR4 signaling. The effects of LPS-TLR4 signaling on cell proliferation and inflammatory cytokines regulation were examined. Specific inhibitors of mitogen-activated protein kinase (MAPK) (extracellular regulated protein kinase [ERK] and p38) signaling pathways were used to investigate the role of each pathway in LPS-TLR4 signaling. TLR4 protein was increased in ESCC tumor tissues compared with the adjacent normal tissues. TLR4 over-expression was significantly correlated with tumor differentiation grade, lymph node metastasis, and UICC stage. LPS-induced activation of TLR4 signaling promoted cancer cell proliferation, increased production of proinflammatory or immunosuppressive cytokines TNF- α, TGF- β and inhibited the anti-inflammatory cytokine IL-10. LPS-TLR4 signaling was associated with the activation of ERK and p38 MAPK signaling pathways. Further inactivation of the two pathways by specific inhibitors attenuated cell proliferation and inflammatory cytokines expression induced by LPS. Our results indicate that LPS-TLR4 signaling in cancer cells contributes to the progression of human ESCC.